1994
DOI: 10.1159/000204262
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pulmonary Amyloidosis Associated with Multiple Myeloma Successfully Treated with Dimethyl Sulfoxide

Abstract: A 57-year-old man with IgG multiple myeloma developed pulmonary infiltration caused by pulmonary amyloidosis, for which continuous transdermal dimethyl sulfoxide (DMSO) treatment was given. After 8 weeks from the start of DMSO treatment, a dramatic reduction of pulmonary infiltration as determined by chest roentgenogram was observed, and arterial blood gas levels were improved. No serious side effect of DMSO was encountered. We conclude that a therapeutic trial with transdermal DMSO administration brought abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…DMSO, an industrial solvent, caused partial or total disappearance of experimentally induced amyloid deposits in mice (Hanai et al, 1979), and therapeutic trials on patients with amyloidosis indicated that prolonged treatment with DMSO may be effective in certain types of systemic amyloidosis (Isobe et al, 1976;Iwasaki et al, 1994). DMSO treatment induced a dramatic reduction in pulmonary infiltration in a patient with IgG multiple myeloma and no serious side-effect of DMSO was encountered (Iwasaki et al, 1994).…”
Section: Gel Mobility Shift Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…DMSO, an industrial solvent, caused partial or total disappearance of experimentally induced amyloid deposits in mice (Hanai et al, 1979), and therapeutic trials on patients with amyloidosis indicated that prolonged treatment with DMSO may be effective in certain types of systemic amyloidosis (Isobe et al, 1976;Iwasaki et al, 1994). DMSO treatment induced a dramatic reduction in pulmonary infiltration in a patient with IgG multiple myeloma and no serious side-effect of DMSO was encountered (Iwasaki et al, 1994).…”
Section: Gel Mobility Shift Assaymentioning
confidence: 99%
“…DMSO treatment induced a dramatic reduction in pulmonary infiltration in a patient with IgG multiple myeloma and no serious side-effect of DMSO was encountered (Iwasaki et al, 1994). Therapy of HMBA, another polar compound that is more potent than DMSO in inducing differentiation of murine erythroleukaemia cells (Reuben et al, 1976), had some success in clinical trials against certain cancers (Young et al, 1988).…”
Section: Gel Mobility Shift Assaymentioning
confidence: 99%
“…DMSO has a number of important properties that make it useful clinically. DMSO has been used successfully to treat urinary (McCammon et al, 1998), pulmonary (Iwasaki et al, 1994), rheumatic (Morassi et al, 1989) and dermatological disorders (Burgess et al, 1998). Because of its anti-inflammatory and antioxidant properties, DMSO has also been used with some success to treat gastrointestinal disorders (Salim, 1992a;Salim, 1992b).…”
Section: Introductionmentioning
confidence: 99%
“…1 In this context, peak plasma concentrations reach values as high as 20 mmol/L. DMSO is also used as a solvent for chemotherapeutic drugs and, due to its antiinflammatory properties, has been successfully used in humans for treating rheumatic, 2 pulmonary, 3 gastrointestinal, 4,5 neurological, 6,7 urinary, 8 and dermatological 9,10 disorders. DMSO further exhibits protective effects in animal models of middle cerebral artery occlusion, 11 cerebral hypoperfusion-related neuronal death, 12 mercuric chloride-induced kidney injury, 13 and chemical liver injury.…”
mentioning
confidence: 99%